Functional Capacity and Inflammatory Mediators in Elderly Residents of Counties with Different Human Development Index - Lygia P. Lustosa; Daniele R. Xavier; Giane A. Ribeiro-Samora; Daniele S. Pereira; Adriana N. Parentoni; Ronaldo L. Thomasini; Leani S. M. Pereira (Journal of Aging Research, 2020)
A number of studies have indicated that certain factors, including socioeconomic status and education, are associated with the functional health status of the elderly. Another relevant factor in aging is chronic subliminal inflammation, with increased levels of circulating inflammatory cytokines such as interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), and soluble tumor necrosis factor receptor 1 (sTNFR-1), commonly seen in the elderly. High levels of these inflammatory mediators could impair the functional capacity. In this respect, the aim of this cross-sectional study was to compare plasma levels of inflammatory mediators and functional capacity of older women living in three Brazilian counties with different Human Development Index. We evaluated 154 women aged ≥65 years, regardless of race and/or social status. IL-6 and sTNFR-1 plasma levels were measured by ELISA and the functional capacity by the Short Physical Performance Battery (SPPB) test. Comparison among groups was performed using one-way ANOVA with Bonferroni post hoc correction, Kruskal–Wallis, and Mann–Whitney U tests. Women that lived in one of the counties with high HDI had lower functional capacity (p<0.001). The population from the county with the highest HDI had lower plasma levels of sTNFR-1 (p<0.05). There was no significant difference in plasma levels of IL-6 (p>0.05). Besides this, women from the counties with lower HDI had a higher number of self-reported diseases and higher income (p<0.05). Women that lived in the county with the highest HDI had a higher average education level (p<0.05). The results showed differences in functional capacity and plasma levels of sTNFR-1 between the counties. In addition, the level of education, family income, and number of self-reported diseases show regional diversities in the aging process, suggesting these factors having an influence on inflammatory mediators and functional capacity.